A Comparative-Lexical Analysis of Kinship Terminologies in Urdu and English (Journal of Asian Development Studies, 2026)
This paper explores the use of kinship terminologiesin English and Urdu by attempting a comparative-lexical analysisusing Morgan’s (1871) classification of kin into consanguineal and affinal relatives. In other words, the conceptual framework of the paper is based on Morgan’s (1871) notion of the patterns of kinship system while the methodological framework is comparative-lexical. The sample consists of three media textsincluding a drama and a film from English and a drama from Urdu.It was found that kinship works in the same way in both the languagesthatfollowdifferent patterns of kinship:English is Dravidian while Urdu is Sundanese. It is suggested that this is because of the difference in the notionsof family unit (nuclear/ joint) andtheir approach to life,individual and/ or community-based. Thepaperisintended todeepen understanding of the kinship terminologies in both languagesin the absence of anyearlier contrastive study of both the languages. It also intends to add meaningfully to the fields of Linguistics, Anthropology, and Sociology.